Synergisms Via Hydrogen Spillover Between Some Transition Metals During Hydrodesulphurization: Increased Activity Towards Conversion of Refractory Molecules - Gil-Llambias, F; Villarroel-Jorquera, M; Villarroel-Jorquera, M (Elsevier B.V., 2011)
The synergism effects by hydrogen spillover on MD//Re stacked bed systems and MD (MD = Mn/?-Al2O 3, Fe/?-Al2O3, Co/?-Al 2O3, Ni/?-Al2O3, Cu/?-Al2O3 or Zn/?-Al2O 3) on two real diesel feeds with different sulphur contents, have been studied. The total sulphur content and the concentration of six refractory molecules present in the feeds were determinated. The dependence of the synergism with the position of the MD in the periodic table describes a volcano curve with a maximum in Co//Re and Ni//Re pairs. This behavior was observed with both feed and with these six refractory molecules. Furthermore, the activity on Co//Mo, Co//W and Co//Re stacked bed systems of 4-MDBT and 4,6-DMDBT was studied. Results show that spillover factor is higher in 4,6-DMDBT than 4-MDBT, suggesting that Hso can play an important role in improving current state of the art catalysts with respect to the elimination of refractory sulphur molecules. Crown Copyright © 2011 Published by Elsevier B.V. All rights reserved.